Setenta y cinco años de sufragio femenino en España, perspectiva constitucional - Figueruelo Burrieza, Ángela (2023)
The purpose of this article is to analyze, from a new point of view, the history of female suffrage in Spain, from the moment it was recognized 75 years ago up to today. Discussions of this subject show a remarkable absence of the principle of equality, which is considered essential in modern constitutionalism. It was only after the approval of the Spanish Constitution in 1978 -which was written without a gender perspective- that the above mentioned liberal principle was introduced with its full meaning. In light of the postulate of the Rule of Law, it becomes necessary to extend material equality to voting rights, in order to end historical discrimination suffered by women. We support a constitutional reform that introduces privacy in the public sector so that women can, in practice, become true legal subjects.